Fast detection of Southern tomato virus by one-step transcription loop-mediated isothermal amplification (RT-LAMP) - Elvira-González, Laura; Puchades, Andrés V.; Carpino, Caterina; Alfaro-Fernández, Ana; Font-San-Ambrosio, Isabel; Rubio, Luis; Galipienso, Luis (2018)
Southern tomato virus (SW) is a double stranded RNA (dsRNA) virus belonging to genus Amalgavirus (family Amalgamaviridae) which has been detected in tomato plants showing stunting, fruit discoloration and size reduction. A one-step reverse-transcription loop-mediated isothermal amplification (RT-LAMP) assay was developed for the detection of SW in total RNA or sap extracts (obtained just by grinding in buffer) from SW-infected tomato plants by using a set of three primers pairs which were designed to the sequence of the SW putative coat protein. Amplification products were visualized by gel electrophoresis or direct staining of DNA. The sensitivity of RT-LAMP was identical to that of the conventional RT-PCR and less affected by the presence of polymerase inhibitors. SW was detected by RT-LAMP in different tomato tissues, i.e. leaves, roots, fruits and seeds. Also the virus was successfully detected by RT-LAMP from sap extracts obtained from field tomato plants whereas conventional RT-PCR did not. Results of this work show that RT-LAMP is a specific, rapid and cheap procedure to detect SW and it could be implemented on field surveys and sanitation programs. (C) 2016 Elsevier B.V. All rights reserved.